Advantages of retrofitting old electric buses and minibuses. (September 2017) - Alessandrini, Adriano; Cignini, Fabio; Ortenzi, Fernando; Pede, Giovanni; Stam, Daniele
Abstract: Old electric buses and minibuses equipped with obsolete energy storage systems are today circulating on the roads all over the world. A minibus prototype equipped with Ion-Lithium batteries developed in the ENEA Casaccia Research Centre demonstrated that an old minibus can be retrofitted by replacing the old lead acid batteries pack with a new pack assembled with LiFePO4 electrochemistry. The new batteries provide sufficient power to the electric motor, an amount of energy to cover nearly 30 kilometers with a full charge, with a new battery load of 50% of the previous battery pack. The new technology allows fast charging, thus solving the problem linked due to the long periods requested to charge of the conventional batteries. For example during public transport service, the minibus can be charged with only twenty minutes, allowing such operation at the terminus while waiting for the passengers. A "depleting" strategy can be applied in order to allow the minibus to be operating all the day with several charges at the stops. In this paper, the performance of a retrofitted minibus in comparison with the same minibus equipped with old generation batteries are reported. The economic benefits for the retrofitted minibus in comparison with a new minibus purchased from factories are also reported.